Kluczowe kompetencje ICT w organizacji zorientowanej na zarządzanie wiedzą - Adamczewski, Piotr (Wydawnictwo Uniwersytetu Rzeszowskiego, 2011)
W artykule omówiono rolę, jaką w nowoczesnych organizacjach odgrywają kluczowe kompetencje w zakresie zarządzania wiedzą w organizacjach społeczeństwa informacyjnego. Zasadnicze relacje gospodarcze realizowane są bowiem w warunkach e-biznesu, czyli sieciowego funkcjonowania partnerów rynkowych z wykorzystaniem ICT.

Traditional human-based activities are increasingly challenged by Information and Communication Technology (ICT). This paper discusses how to deploy key competencies of ICT in knowledge management (KM). A KM-systems offers integrated services to deploy KM instruments for networks of participants, i.e. active knowledge workers, in knowledge-intensive business processes along the entire knowledge life cycle in information society.